Profiling the Bladder Microbiota in Patients With Bladder Cancer - Parra-Grande, Mónica; Oré-Arce, Martín; Martínez-Priego, Llúcia; D’Auria, Giuseppe; Rosselló-Mora, Ramón; Lillo, Marta; Sempere, Andrea; Lumbreras, Blanca; Sánchez-Hellín, Victoria (Frontiers in Microbiology, 2022)
Evidence suggests that microbiota may contribute to the pathogenesis of several diseases, including cancer. In the case of bladder cancer, preliminary studies have found alterations in the urinary microbiota of patients with urothelial carcinoma compared with healthy individuals. Conversely, the urinary microbiota differ between men and women, and it has been hypothesized that these differences are associated with the lower incidence of bladder cancers in women. The objective of this study was to characterize the bladder microbiota in paired samples of tumor and nontumor mucosa of patients with malignant bladder neoplasia using next-generation sequencing. In addition, we aimed to study potential differences in microbial composition in tumor samples according to clinical and pathological variables, and to determine possible microbial profiles. We found significant differences in microbial richness at the genus level, with a higher richness observed in the nontumor compared with the tumor mucosa. It was also shown that Actinobacteria were significantly more enriched in the nontumor compared with the tumor mucosa (P = 0.014). In the multivariate analysis, we found significant differences in microbial composition according to tumor grade (P = 0.03 and 0.04 at the phylum and genus levels, respectively). Moreover, we detected a higher microbial richness in nontumor vs tumor tissues which agrees with the global assumption that microbial richness is an indicator of health. The greater abundance of members of the Actinobacteria phylum in the nonneoplastic bladder mucosa samples supports the hypothesis that a higher abundance of Actinomycetes is associated with a lower rate of bladder cancer in women and suggests a protective role for these microbiota. We detected a microbial profile that was enriched for Enterococcus in low-grade tumors. Finally, we identified the presence of two clusters in the microbial composition of the tumor mucosa samples, significantly enriched for the genera Barnesiella, Parabacteroides, Prevotella, Alistipes, and Lachnospiracea_incertae_sedis (Cluster 1), or Staphylococcus (Cluster 2). Further longitudinal studies are needed to assess the role of the bladder microbiota in carcinogenesis.